The Effect Of Long Term Debt To Equity Ratio And Company Size On Share Price At PT Japfa Comfeed Indonesia Tbk For The Period 2015-2024 - Aulia, Syara Irna; Fadli, Achmad Agus Yasin (Jurnal Fokus Manajemen, 2025)
This study aims to determine the Long Term Debt to Equity Ratio and Company Size on the Share Price of PT Japfa Comfeed Indonesia Tbk for the period 2015-2024, both partially and simultaneously. This study uses quantitative methods with secondary data. The research population is the financial statements of PT Japfa Comfeed Indonesia Tbk, and the sample is in the form of financial position reports and stock overviews for 2015-2024. Data analysis was performed with multiple liner regression using SPSS v25. The F test shows that LTDER and Company Size simultaneously have a significant effect on stock prices. The T test results show that LTDER has a negative and partially significant effect on stock prices, while Company Size has no significant effect partially on the stock price of PT Japfa Comfeed Indonesia Tbk for the period 2015-2024.